Facing the Past: Engendering the Study of Iron Age Celtic Human Imagery in Continental Europe - (:unkn) unknown (My University, 2021)
Iconography is an important tool in understanding the past because it may express apeople’s understanding of the world through representations of stories or figures, including human beings. The continental early Iron Age Celts left behind no written sources but did leave iconographic representations of humans in the form of full bodies as well as heads. How the Celts saw their world and how they perceived and gendered other humans or anthropomorphic beings can be partially accessed via these representations. This thesis examines a representative sample of statues and figures from Iberia, Gaul, and Central Europe from an intersectional perspective focused on status and gender. Details such as facial features, jewelry, or weapons have often been associated with certain genders or statuses, but to date, no systematic comparative analysis has been carried out to determine whether there are any geographic or temporal patterns in these representations. Items such as arm rings and belts have been reevaluated to test the idea that status may have been as important as gender in such representations. This study was able to demonstrate that images with masculine or male features appear more frequently in stone or metal than those with feminine or female features and that facial hair in emic imagery challenges the stereotypical view presented by Mediterranean sources that emphasize moustaches rather than beards. The presence and placement of belts and arm rings in iconographic representations likewise does not conform to expected patterns from mortuary contexts, possibly due to differential preservation. This project opens a dialogue for iii future analysis of gendered objects through iconographic analysis. An intersectional analysis of human figural representation in Celtic iconography has the potential to expand our understanding of gender in Iron Age Europe by interrogating objects intended to depict human or anthropomorphic beings.
Keywords: Celts; Europe; Gender; Iconography; Iron Age